Smart design of coupling scissors-type bridge. (April 2021) - Chanthamanivong, Khongkham; Ario, Ichiro; Chikahiro, Yuki
Abstract: Historical disasters have affected infrastructure, such as roads and bridges. However, during rescue procedures, the victims must be reached promptly and safely. Scissors-type structures have been extensively used, mostly in the development of space structures, and are an important consideration in terms of dynamic behaviour owing to their reduced gravity loading. Moreover, additional factors must also be considered. In this study, a new coupling scissor-type bridge that combines different sizes of scissors structures is proposed to eliminate the disadvantage of heavy traffic loading and provide a faster way to cross a river. Previous studies have demonstrated that this bridge structure is sensitive to vibration in the horizontal axis instead of the vertical axis, because there are many nodal points. Thus, the combination of structures can enhance the capacity of the structure and overcome static and dynamic problems. The theoretical and numerical results clearly demonstrate that the proposed structure improves the safety of the bridge. Additionally, by applying additional reinforcing members, the coupling scissors-type structure (CSCI) can increase the capacity of the static and dynamic loading. The numerical and simulation results are significant and clearly demonstrate the benefit provided by the proposed structure.